Factors Responsible For Discriminating Between High and Low Adopter Categories of Shrimp Farmers - P.S., Swathi Lekshmi; N., Balasubramani; Vimala, D.D.; K., Chandrakandan (Fishery Technology, 2025)
Shrimp farming on a commercial scale has come to be the main stay, of the coastal economy of the country. Scientific Shrimp farming is characterised by the adoption of improved technologies for getting a better yield both in terms of quantity and quality. Adoption of improved technologies is dependent upon a host of factors such as the perceived attributes of the technology, the cost of the technologies and the policy environment in which the technologies are adopted. Among these factors, certain factors help to discriminate between high and low adoption categories. These are vital from the point of view of technology development and refinement. In this study 60 shrimp farmers of Nellore district of Andhra Pradesh were studied for identifying the factors responsible for discriminating the high and low adoption categories of shrimp farmers. The findings revealed that, the variables such as attributes of shrimp culture technologies such as efficiency and feasibility of technologies had substantial importance in the classification of shrimp farmers into high adopter category and low adopter category. Further, it was observed that of the 60 shrimp farmers studied, 31 belonged to high adopter category and 29 belonged to the low adopter category.